Exploring the importance of work outcomes in gynaecological patients. (2nd March 2022) - Sparks, R; Ahluwalia, S; Aslam, I; Austin, G; Fitzgerald, R; Gupta, S; Inyang, D; Khan, A; Opoka, V; Wardere, J; Madan, I; Naleem, S; et al.
Abstract: Background: There has been increasing evidence that physicians in gynaecology are not routinely enquiring about work during consultations. Aims: To explore the effect gynaecological conditions can have on work functioning, the importance of work outcomes among patients and whether work considerations are discussed during clinical consultations. Methods: A cross-sectional survey was administered to employed patients attending a gynaecological clinic at Guy's Hospital. The survey assessed four areas: demographics, gynaecological condition (including self-assessed severity), work status and perceived impact of the condition on work functioning and job satisfaction. Simple descriptive analysis and statistical techniques were used to interpret the data. Results: One hundred and six participants participated (mean age: 37.49 ± 9.09). About 95% found it important to be able to work whilst receiving treatment and 82% of patients had reported at least a slight impact on their working ability due to their condition. Of the 31 patients for whom it was their first appointment, 77% said it would be useful to discuss the possible impacts their gynaecological condition could have on their work. About 66% (19/29) of the participants attending a follow-up appointment reported that their doctor had not discussed their work with them. Conclusions: The symptoms of gynaecological conditions can impact patients' ability to work. There is a lack of useful discussion from doctors about the perceived impact gynaecological conditions can have on a patient's ability to work, despite patients finding it important to be able to remain or return to work.